2024
DOI: 10.3390/nu16050668
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Caffeinated Coffee on Cross-Country Cycling Performance in Recreational Cyclists

Daniel Trujillo-Colmena,
Javier Fernández-Sánchez,
Adrián Rodríguez-Castaño
et al.

Abstract: The ergogenic effects of acute caffeine intake on endurance cycling performance lasting ~1 h have been well documented in controlled laboratory studies. However, the potential benefits of caffeine supplementation in cycling disciplines such as cross-country/mountain biking have been rarely studied. In cross-country cycling, performance is dependent on endurance capacity, which may be enhanced by caffeine, but also on the technical ability of the cyclist to overcome the obstacles of the course. So, it is possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Caffeine, being a significant sports nutrition supplement, has consistently garnered considerable attention [109]. Early investigations have substantially propelled research advancements in this domain and contributed to the widespread utilization of caffeine in daily practices [110][111][112][113][114]. While the majority of studies have indicated caffeine's performanceenhancing effects across various athletic disciplines, some have yielded inconclusive results regarding its efficacy in certain performance metrics [115].…”
Section: Considerations For Timing Factors In Future Caffeine Researchmentioning
confidence: 99%
“…Caffeine, being a significant sports nutrition supplement, has consistently garnered considerable attention [109]. Early investigations have substantially propelled research advancements in this domain and contributed to the widespread utilization of caffeine in daily practices [110][111][112][113][114]. While the majority of studies have indicated caffeine's performanceenhancing effects across various athletic disciplines, some have yielded inconclusive results regarding its efficacy in certain performance metrics [115].…”
Section: Considerations For Timing Factors In Future Caffeine Researchmentioning
confidence: 99%